Quality of routine health and nutrition data in Ethiopia: A systematic review - Zerfu, Taddese Alemu; Genye, Tirsit; Tareke, Amare Abera (2025)
Background High-quality data are vital for informed decision-making, enhancing population health, and achieving comprehensive insights. However, there is limited understanding of the consistency and reliability of routine Health Management Information System (HMIS) including nutrition data across diverse regions in Ethiopia. This study systematically reviewed the existing literature to address these knowledge gaps.